METODE DAKWAH USTADZ SUPRAPTO PADA BAJINGAN - Afif Rohman Jaya; Mukhammad Baharun; Kautsar Wibawa (Maddah : Jurnal Komunikasi dan Konseling Islam, 2020)
The method of da'wah is a method, approach, or process in conveying da'wah that is calling out or inviting others, in order to practice the teachings of Islam or the activities of delivering Islamic teachings from one person to another, which is carried out consciously and intentionally in various planned ways. , so that the goal of finding happiness in life based on the pleasure of Allah SWT can be achieved. The purpose of this study is to describe the method of propaganda Ust. Suprapto to Bajingan in Campalok Jatisari, Arjasa sub-district, Situbondo district. The results showed that Ust. Suprapto in da'wah uses several methods, namely the mujadalah method which is applied by conducting discussions with the bastards and giving advice to thugs. The second is the bil hikmah method. In this method Ust. Suprapto jumps into the field to visit the bastards and show wisdom. Third is the method of mau'idzhah al-hasanah. this method Ust. Suprapto apply when there are mujahadah activities by giving enlightenment to the bastards.